Technology - Based Simulation Learning of Classroom Enhancing Students' Learning & Teachers' Practical Performance - Gamal Ahmed Ahmed Abdullah Alawi (Taez University, 2023)
Using Technology-based simulations that are interesting, easy to use by participants, and shorting the time of technical teachers in bringing the technical materials to be used in learning anywhere and anytime. The technology of simulation learning is the most significant tool of the information age and has increasingly been used in each stage of the education system. The main objective of this study is to enhance students' learning performance depending on using simulation techniques. The participants were three hundred participants participated in this study. Using simulation suggestions for participants' opinions and attitudes were discussed. This paper has been designed to study the development that is happening for the participants of the classroom towards the simulation lab usage in three dimensions which are abilities, practical skills, and knowledge they have. The interaction between these dimensions is the key purpose of this study to merge technology in existing education and introduce simulation technology as an important tool to support new ways of practical studies. A model, that explains the effect of TSU, TAS, and TPU on learning, is generated and tested. Using the AMOS 18 (Analysis of Moment Structures) program, it explains (70%) of TSU TOOLS, (77%) of TPU TECHNOLOGY, and (60 %) of TAS, with good model fit. The findings accept all hypotheses.